Risk factors of recurrent diabetic foot ulcers based on the delphi method - Haryanto Haryanto; Makoto Oe; Tutur Kardatun; Ramadhaniyati Ramadhaniyati; Lestari Makmuriana; Yunita Sari; Wida K Bhakti (Iranian Journal of Nursing and Midwifery Research, 2024)
Background: The risk factors for recurrence are poorly understood. The purpose of study is to investigate the risk factors that contribute to the recurrence of diabetic foot ulcers. Materials and Methods: This is a cross-sectional study, and the two-phase Delphi method was used. A category was developed to investigate the risk factors of recurrent diabetic foot ulcers by experts. The recurrent items with risk factors were analyzed. Furthermore, the risk factor variables were clinically tested for inter-rater reliability agreement. Fourteen experts and two patients were included from February 15 to September 28, 2020, Indonesia. Results: There were 13 risk factors for recurrent diabetic foot ulcers. The mean authority coefficient was 0.71. The positive coefficients were 100% and 78%, respectively. The Kendall coordination coefficient was statistically significant (p < 0.01), and inter-rater reliability agreement was perfect (1.00). Conclusions: This study found some risk variables related with recurrent diabetic foot ulcers, which might serve as guidance to prevent future recurrences.